2018
DOI: 10.5604/01.3001.0011.8183
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with endoscopic sleeve gastroplasty in Poland

Abstract: Compared to laparoscopic sleeve gastrectomy, endoscopic sleeve gastroplasty is substantially less invasive. Also, it requires shorter procedure time and shorter hospital stay. Data from other medical centres demonstrate somewhat lower dynamics of total body weight loss but these results need to be verified in a long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Eighty‐eight percent of patients achieved >15% TBWL at 12 months with no serious adverse events documented. Additional international studies have shown similar results 42–44 . A systematic review and meta‐analysis has also been published, demonstrating a TBWL of 15.1%, EWL of 57.7%, and pooled adverse event rate of 2.2% 45 .…”
Section: Fda Approved Endoscopic Therapiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Eighty‐eight percent of patients achieved >15% TBWL at 12 months with no serious adverse events documented. Additional international studies have shown similar results 42–44 . A systematic review and meta‐analysis has also been published, demonstrating a TBWL of 15.1%, EWL of 57.7%, and pooled adverse event rate of 2.2% 45 .…”
Section: Fda Approved Endoscopic Therapiesmentioning
confidence: 78%
“…Additional international studies have shown similar results. [42][43][44] A systematic review and meta-analysis has also been published, demonstrating a TBWL of 15.1%, EWL of 57.7%, and pooled adverse event rate of 2.2%. 45 A more recent multi-center ESG trial (MERIT Trial), is ongoing at the time of this review.…”
Section: Endoscopic Tissue Appositionmentioning
confidence: 99%